Mobile Telephony and the Democratic Process in Nigeria: Wider Coverage, Limited Impact (Journal of Management and Social Sciences, 2017)
AbstractThe explosive growth and widespread presence of mobile telephony in Nigeria has attracted comments and research focusing on its social, economic, technological and cultural implications. However, scant attention, mostly newspaper comments, has been given to the contributions of mobile telephony to the democratic process in Nigeria. Given the centrality of communication to democracy and the nascence of Nigerian democracy, filling this gap is a worthwhile task. Using a questionnaire administered onliterate phone users, and interviews with non-literate users, selected through a combination of purposive and convenience sampling techniques, we addressed the question: in what ways and to what extent has mobile telephony promoted critical democratic activities in Nigeria? There is widespread presence of mobile phone among respondents but limited use and limited impact. Only 49.7% of literate users used their phones for anything beyond sending and receiving calls and text messages; non-literate users had to depend on literate others for nearly everything pertaining to mobile phone use. Mobile phones were used in campaigns, provided information but not conviction about voting decisions: they did not make 70.8% of the respondents to vote or not to vote in certain ways. Mobile phones were found to be weak for post-election engagements and accountability as elected politicians were said to change their phonelines or bar incoming calls. We conclude that there is widespread application of the mobile phone to the democratic process in Nigeria but the impact of this application is only limited.Â Keywords Â Mobile telephony, Nigerian democracy, impact of mobile telephony, Nigerian politics